Innovative Development of Low-Carbon, Clean, and Intelligent Aluminum Metallurgy - Jie Li; Xiaowei Huang; Guihua Liu; Fengqin Liu; Jiaqi Li; Hongliang Zhao; Hongliang Zhang (中国工程科学)
Aluminum is the most widely used non-ferrous metal. Promoting the low-carbon, clean, and intelligent development of the aluminum metallurgy is crucial for implementing the new development philosophy and cultivating new quality productive forces. This study delves into the historical background and projected trajectory of China's aluminum industry, shedding light on the ecological links and pivotal intricacies of aluminum smelting processes. Subsequently, the study conducts a thorough analysis of the technical status and prevailing challenges across three crucial domains: the energy-saving, low-carbon, and intelligent aluminum electrolysis; the low-carbon and clean production of alumina using aluminum-containing resources; and the safe disposal and recycling of hazardous solid wastes in aluminum industry. Based on a thorough assessment of resources, energy, and environmental factors, we establish fundamental principles for fostering the innovative development of a low-carbon, clean, and intelligent aluminum metallurgy. For each critical process, we outline an innovative development roadmap, highlight key technologies, and set ambitious development goals for 2035. To achieve these goals, the following measures are proposed: improving the national policy system, formulating a high-quality standards system, enhancing the industrial security system, accelerating the green and low-carbon technology transformation, and strengthening the nation through human resources.